The externalities of credit default swaps on stock return synchronicity. Issue 1 (14th August 2019) - Zhao, Ran; Zhu, Lu
Abstract: We examine the externality effect of customer firms' credit default swap (CDS) trading on the stock price informativeness of supplier firms. Our empirical results show that firms with a high proportion of sales to CDS referenced customers tend to have more firm‐specific embedded information in their stock prices and thus higher stock price informativeness, which is associated with a lower level of stock return synchronicity. We provide new evidence of CDS trading externality on equity market information environments along the supply chain.